A renewable natural cotton derived and nitrogen/sulfur co-doped carbon as a high-performance sodium ion battery anode. (June 2018) - Yang, Chenghao; Xiong, Jiawen; Ou, Xing; Wu, Chun-Fu; Xiong, Xunhui; Wang, Jeng-Han; Huang, Kevin; Liu, Meilin
Abstract: Here we report a new N/S co-doped carbon nanosheets derived from a renewable natural cotton source and its performance as an anode for SIBs. The electrochemical testing shows that the new carbon anode outperforms other major carbon-based anodes in sodiation capacity (482.1 mAh g −1 at 0.1 A g −1 ), rate performance (375.6, 357.8, 340.5, 324.1 mAh g −1 at 1.0, 2.0, 5.0 and 10.0 A g −1, respectively) and cycling stability (351.1 mAh g −1 at 2.0 A g −1 for 600 cycles). The defects, enlarged d-spacing, reduced Na + diffusion barrier and increased electronic conductivity of the fabricated N/S co-doped carbon nanosheets are responsible for the excellent Na + storage property, while the pseudocapacitive behavior of Na + storage contributes to their high rate performance. This work demonstrates a low-cost path forward to fabricate high-performance carbonaceous anode materials for SIBs. Graphical abstract: Highlights: Renewable cotton as a source of carbon for anode of sodium-ion batteries. Improved electrical properties and enlarged d-spacing of carbon by co-doping of nitrogen and sulfur. Pseudocapacitance is responsible for the high rate performance.